Integrasi Pembelajaran Pendidikan Agama Islam Dengan Gerakan Pramuka Dalam Meningkatkan Altruistik Peserta Didik - Irfan Kuncoro (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
This research is motivated by the not yet achieving the massive goals of education, especially being faithful, pious and noble. The decadence of altruism can be seen in MA Sunan Pandanaran, an example of which is apathy among students. The solution is to